2022
DOI: 10.3390/w14060932
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Hydraulic Retention Time and Area of Biological Settling Ponds for Super-Intensive Shrimp Wastewater Treatment Systems

Abstract: Biological settling ponds are a practicable approach for treating super-intensive shrimp aquaculture wastewater for almost all shrimp producers in the Vietnamese Mekong Delta (VMD). The optimization of the hydraulic retention time (HRT) of biological settling ponds plays a crucial role in establishing the stability of outflow wastewater quality and suitability of the settling pond area (SPA). This study aims to suggest appropriate HRT and SPA for super-intensive shrimp wastewater treatment systems based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Previous publications have revealed that the ISF wastewater (including wastewater from water exchange and sludge from siphoning) from intensive and super-intensive shrimp farming often contains high levels of biodegradable organic compounds and dissolve nutrients (Boopathy, 2018;Nguyen et al, 2022;. Average COD levels were in the 466 -1,854 mg/L range; while concentrations of TAN, TKN, and TP were in a typical range of 29.8 -101 mg/L, 9.63 -161 mg/L, & 17.3 -92 mg/L, respectively (Boopathy, 2018;Tran et al, 2022;Nguyen et al, 2022). The sludge characteristics in this study were much higher than the results of previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous publications have revealed that the ISF wastewater (including wastewater from water exchange and sludge from siphoning) from intensive and super-intensive shrimp farming often contains high levels of biodegradable organic compounds and dissolve nutrients (Boopathy, 2018;Nguyen et al, 2022;. Average COD levels were in the 466 -1,854 mg/L range; while concentrations of TAN, TKN, and TP were in a typical range of 29.8 -101 mg/L, 9.63 -161 mg/L, & 17.3 -92 mg/L, respectively (Boopathy, 2018;Tran et al, 2022;Nguyen et al, 2022). The sludge characteristics in this study were much higher than the results of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Shrimps were intensively cultured according to a three-stage process with an initial stocking density of 1,000 fish/m 2 and gradually decreasing stocking density to about 400 -500 shrimp/m 2 in stage 2 and about 150 -200 shrimp/ nutrients. Investigating 20 typical ISF ponds in the MK, Tran et al (2022) reported that average levels (mg/L) of total suspended solid (TSS), chemical oxygen demand (COD), total ammonia nitrogen (TAN), total Kjeldahl nitrogen (TKN), total phosphorous (TP) in sludge were 3. 423, 1.854, 101, 161, and92, respectively.…”
Section: Collecting Sludgementioning
confidence: 99%